2003
DOI: 10.1039/b211008c
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and intermolecular fluorescence quenching of N-activated 4,5-dimethoxyphthalimides by sulfides, amines, and alkyl carboxylates

Abstract: The fluorescent 4,5-dimethoxyphthalimides 1-10 were applied as sensors for intra- and intermolecular photoinduced electron transfer processes. Strong intramolecular fluorescence quenching was detected for the thioether 2 and the tertiary amine 3. The fluorescence of the carboxylic acids 4-7 is pH-dependent accounting for PET-quenching of the singlet excited phthalimide at pH > pKs. At low pH, chromophore protonation might contribute to moderate fluorescence quenching. The arylated phthalimides 9 and 10 show re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…These probes take advantage of the highly reactive natural amino acid methionine that is converted to the sulfoxide, a process that can also be reversed by methionine sulfoxide reductase. In intermolecular quenching studies, we have already identified the strong intermolecular fluorescence quenching of fluorescent phthalimides by thioethers . In the new probes, donor‐substituted phthalimides are used as fluorophores and methionine derivatives as the 1 O 2 ‐sensitive parts .…”
Section: Resultsmentioning
confidence: 99%
“…These probes take advantage of the highly reactive natural amino acid methionine that is converted to the sulfoxide, a process that can also be reversed by methionine sulfoxide reductase. In intermolecular quenching studies, we have already identified the strong intermolecular fluorescence quenching of fluorescent phthalimides by thioethers . In the new probes, donor‐substituted phthalimides are used as fluorophores and methionine derivatives as the 1 O 2 ‐sensitive parts .…”
Section: Resultsmentioning
confidence: 99%
“…18 Much to our delight, 1c turned out to be a reactive substrate for the photodecarboxylation with 3,4,5-trimethoxyphenylacetate 2d (Scheme 4). 19 In this special case, application of the electron-rich aryl group in the donor substrate seems to accelerate the electron transfer process.…”
Section: Methodsmentioning
confidence: 98%
“…The fluorescence quenching of the model compound 3,4-dimethoxy N-methyl phthalimide (DMMP) by dimethyl sulfide was recently investigated and dynamic quenching with a Stern-Volmer constant K SV of 59 M À 1 was determined in methylene chloride. [15] In order to correlate this with the compounds described in this publication, the Nbutyl derivative 6 was investigated and also fluorescence lifetimes were determined for 6 and the N-methyl derivative in acetonitrile. In acetonitrile, the undisturbed fluorescence of phthalimide 6 decays monoexponential with τ F = 32 ns and is quenched by external dimethylsulfide (Figure 7).…”
Section: Intermolecular Fluorescence Quenchingmentioning
confidence: 99%
“…[12][13][14] An especially successful approach was the 4,5dialkoxyphthalimide that shows strong fluorescence with quantum yields near to 100 %. [15] Strongly fluorescent phthalimides that also constitute very strong reductants in the excited singlet states have been developed as excellent sensors for anions such as fluoride, [16,17] or cyanide. [18] Recently, we have developed phthalimide probes for singlet oxygen and hydrogen peroxide that operate by fluorescence ON effects and were based on 4,5-dialkoxyphthalimides with internal fluorescence quenching groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation